Identificamos información importante de un texto narrativo - Palomino Villoslada, Mereida (2019)
This lesson plan of professional qualification has a scientific, philosofical and psycopedagogical support._x000D_ We use the scientific and philosophical support to develop the written communication._x000D_ In the psycopedagogical support this lesson plan has the psychological and pedagogical support that help the students to develop their scientific competences.